Adaptation to maternal role and infant development: a cross sectional study. (27th May 2018) - Khandan, Samine; Riazi, Hedyeh; Amir Ali Akbari, Sedigheh; Nasiri, Malihe; Montazeri, Ali
Abstract: Objective: To assess the correlation between adaptation to maternal role (AMR) and infant development. Background: Maternal role is an important key in infant's care and development. Previous findings demonstrated an inconsistency in the effect of the mother's adaptation on each domain of infant's development. Methods: This cross-sectional study was conducted on 260 healthy mothers and healthy infants attending health centres affiliated to Shahid Beheshti University of Medical Sciences in Tehran in 2016. Data were collected using the 'AMR in Iranian Primiparous Women Questionnaire' and the 'Ages and Stages Questionnaire' (ASQ). The correlation between adaptation to maternal role and infant development was assessed using partial correlation analysis adjusted for age and gender. Results: In all 14 infants had developmental delay giving a prevalence rate of 5.4%. The mean AMR score was 123.9 (SD =13.1) and there was no significant correlation between the AMR total score and infant development ( r = 0.06, p = 0.27). However, significant correlation were observed between some aspects of adaptation to maternal role and infant development such as the 'support and consolidation of the couple's relationship' and 'communication' ( p = 0.04); the 'concern and anxiety' subscale and 'gross motor skills' ( p = 0.03), the 'attachment to the child' subscale and 'personal-social development' ( p = 0.02) and the 'emotional development' subscale with 'personal-social development' domain ( p = 0.004). Conclusion: The findings suggest that correlation exists between some aspects of adaptation to maternal role and infant development.